A prospective, randomized, double-blind entropy-guided approach to evaluate the efficacy of different doses of dexmedetomidine with propofol versus fentanyl with propofol for ProSeal laryngeal mask airway insertion - Mahantesh Mudakanagoudar; Bhavana Koppad; Manjunath Shivapujimath; Meghana Hanagandi (Journal of Krishna Institute of Medical Sciences University)
Background: Airway management with Proseal Laryngeal Mask Airway (PLMA) is increasingly being used. PLMA insertion requires adequate jaw relaxation and depth of anesthesia while maintaining hemodynamic stability. Opioids including fentanyl and alpha-2 agonists like dexmedetomidine are increasingly being used with propofol for the same. Aims and Objectives: To assess efficacy of different dexmedetomidine doses in providing optimal conditions for insertion of PLMA, compare with that of fentanyl, and correlate with Entropy. Material and Methods: Prospective double-blind, randomized study was conducted on 120 individuals between 18 - 65 years of ASA I /II and had been randomized into 4 groups: Group 1 - Dexmedetomidine 0.5 μg/kg, Group 2 - Dexmedetomidine 0.75 μg/kg, Group 3 - Dexmedetomidine 1μg/kg and Group 4 - Fentanyl 2μg/kg. Standard anesthesia monitors with entropy sensors were attached. Study drug was administered over 10 minutes, followed by a propofol bolus; once the State Entropy was less than 50, PLMA was inserted after assessing jaw relaxation. Results: Both groups were similar in demographic data and insertion conditions. Systolic blood pressure, mean arterial pressure, and diastolic blood pressure reductions were larger in group fentanyl. Apnea time was more infentanyl group than the dexmedetomidine group but was not statistically significant. Conclusion: Different doses of dexmedetomidine in conjunction with propofol provide identical PLMA insertion settings as fentanyl propofol combination, better maintenance advantage of hemodynamics, and less apnea incidence with adequate depth of anesthesia.